High TSPAN8 expression in epithelial cancer cell‐derived small extracellular vesicles promote confined diffusion and pronounced uptake - Teng Wang (Taylor & Francis Group, 2021)
Abstract Small extracellular vesicles (sEVs) play a key role in intercellular communication. Cargo molecules carried by sEVs may affect the phenotype and function of recipient cells. Epithelial cancer cell‐derived sEVs, particularly those enriched in CD151 or tetraspanin8 (TSPAN8) and associated integrins, promote tumour progression. The mechanism of binding and modulation of sEVs to recipient cells remains elusive. Here, we used genetically engineered breast cancer cells to derive TSPAN8‐enriched sEVs and evaluated the impact of TSPAN8 on target cell membrane's diffusion and transport properties. The single‐particle tracking technique showed that TSPAN8 significantly promoted sEV binding via confined diffusion. Functional assays indicated that the transgenic TSPAN8‐sEV cargo increased cancer cell motility and epithelial‐mesenchymal transition (EMT). In vivo, transgenic TSPAN8‐sEV promoted uptake of sEVs in the liver, lung, and spleen. We concluded that TSPAN8 encourages the sEV‐target cell interaction via forced confined diffusion and significantly increases cell motility. Therefore, TSPAN8‐sEV may serve as an important direct or indirect therapeutic target.